Modified food waste for pollutants sorption - Yuen, Mei Lian; Nurfyahfizeh, N.; Ros, A. R.; Tan, Y. P. (Universiti Malaysia Pahang, 2019)
The capability of modified banana peel (MBP) to adsorb Fe ions from synthetic ion solution has been studied. The acidic and basic solution strongly affected the Fe ions adsorption. The effect of contact time and initial ion concentrations revealed that removal efficiency for 15 mg/L Fe ions above 90 % after 2 hours. The size particles for MBP below 106 µm turned out to be the prefer size due to the highest percentage of ions adsorption. MBP appears to be a promising material to purify wastewater.